2005
DOI: 10.1111/j.1600-0668.2005.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Current asthma and respiratory symptoms among pupils in relation to dietary factors and allergens in the school environment

Abstract: Previous school studies performed by us in mid-Sweden, showed that most classrooms did not fulfill the ventilation standards. In this study, most of the classrooms fulfilled the ventilation standard, but despite that had widespread allergen contamination. Most previous studies have focused on cat allergen, but our study has shown that also dog and horse allergens can be risk factors for asthma and allergy in schools. As allergens are transported from other environments, mainly the home environment, the main pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
160
6
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(178 citation statements)
references
References 58 publications
6
160
6
3
Order By: Relevance
“…One of the main source of these fatty acids is butter, which also showed an association with current asthma (Table 4). This result contrasts with that of a Swedish study involving 1014 schoolchildren (age 5-14 years), in which the associations between allergens and respiratory symptoms were more pronounced among those who did not consume butter and who had a low intake of milk (Kim et al, 2005). A similar observation was recorded in the Prevention and Incidence of Asthma and Mite Allergy birth cohort study (2003); after following 2978 pre-school children in the Netherlands for one year, the prevalence of recent asthma and wheezing was found to be lower in children who consumed butter daily than in those who did not (1.5 vs 5.1% for asthma and 7.7 vs 15.4% for wheezing) (Wijga et al, 2003).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…One of the main source of these fatty acids is butter, which also showed an association with current asthma (Table 4). This result contrasts with that of a Swedish study involving 1014 schoolchildren (age 5-14 years), in which the associations between allergens and respiratory symptoms were more pronounced among those who did not consume butter and who had a low intake of milk (Kim et al, 2005). A similar observation was recorded in the Prevention and Incidence of Asthma and Mite Allergy birth cohort study (2003); after following 2978 pre-school children in the Netherlands for one year, the prevalence of recent asthma and wheezing was found to be lower in children who consumed butter daily than in those who did not (1.5 vs 5.1% for asthma and 7.7 vs 15.4% for wheezing) (Wijga et al, 2003).…”
Section: Discussioncontrasting
confidence: 55%
“…Nevertheless, our results are more proximal to the prevalence found in Sweden children (5.9%) from 5-14 years old (Kim et al, 2005), Dutch children (6.5%), who had the same range age than children studied in our study (8-13 years) (Tabak et al, 2006) or One-way ANOVA was used to identify significant differences between children with and without asthma.…”
Section: Discussionmentioning
confidence: 70%
“…This is not surprising since measurements confirm contamination of cat and dog allergens in settled dust in the classrooms regardless of floor cleaning methods and ventilation (Kim et al., 2005; Perzanowski et al., 1999). In our study, when some of the adolescents reported different allergens as asthma triggers, several of the adolescents were bothered by furry animal allergens from classmates’ clothes.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect varied between 25 and 95%, which might be attributed to differences in study design, exposure and outcome measure classification and assessment. Nine studies observed a beneficial effect of fish intake during infancy/childhood and atopic outcomes in those infants/children (32,35,(51)(52)(53)(54)(55)(56)(57) . The reduction in atopy/ allergy risk among these studies ranged between 22 and 80%.…”
Section: N-3 Pufa Eicosanoids and Inflammatory Processesmentioning
confidence: 99%
“…Polyunsaturated oil consumption was associated with increased risk of wheeze in Swedish children (OR = 1 . 91) (35) . A high dietary ratio of n-6 to n-3 PUFA was associated with increased risk of asthma in Australian schoolchildren (OR = 1 .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%